Dietary Chinese herbal formula supplementation improves yolk fatty acid profile in aged laying hens - Zhihua Li; Chengwen Meng; Md. Abul Kalam Azad; Wencao Lin; Jue Gui; Yadong Cui; Wei Lan; Qinghua He; Xiangfeng Kong (Veterinary Quarterly)
Chinese herbal formula (CHF) has the potential to improve the performance of aged laying hens through integrated regulation of various physiological functions. The present study aimed to investigate the effects of dietary CHF supplementation on the yolk fatty acid profile in aged laying hens. A total of 144 healthy 307-day-old Xinyang black-feather laying hens were randomly allocated into two groups: a control group (CON, fed a basal diet) and a CHF group (fed a basal diet supplemented with 1% CHF; contained 0.30% Leonurus japonicus Houtt., 0.20% Salvia miltiorrhiza Bge., 0.25% Ligustrum lucidum Ait., and 0.25% Taraxacum mongolicum Hand.-Mazz. for 120 days). The fatty acid concentrations in egg yolks were analyzed using a targeted metabolomics technology at days 60 and 120 of the trial. The results showed that dietary CHF supplementation increased (p < .05) the concentrations of several saturated fatty acids (SFA, including myristic acid and stearic acid), monounsaturated fatty acids (MUFA, including petroselinic acid, elaidic acid, trans-11-eicosenoic acid, and cis-11-eicosenoic acid), polyunsaturated fatty acids (PUFA, including linolelaidic acid, linoleic acid, γ-linolenic acid, α-linolenic acid, 11c,14c-eicosadienoic acid, eicosatrienoic acid, homo-γ-linolenic acid, arachidonic acid, and docosapentaenoic acid), and fatty acid indexes (total MUFA, n-3 and n-6 PUFA, PUFA/SFA, hypocholesterolemic/hypercholesterolaemic ratio, health promotion index, and desirable fatty acids) in egg yolks. Collectively, these findings suggest that dietary CHF supplementation could improve the nutritional value of fatty acids in egg yolks of aged laying hens, which would be beneficial for the production of healthier eggs to meet consumer demands.